The effect of peer support intervention on improving self-efficacy in adolescents with HIV: A systematic review - Sri Wulan Widyawati; Etty Rekawati; Agus Setiawan; Indah Permatasari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Adolescents with HIV who have low self-efficacy are less likely to adhere to their treatment plans, experience psychological issues, become socially isolated, and make poor treatment management decisions. Peer support therapy is therefore required to raise these teenagers' self-efficacy. Evaluating self-efficacy is crucial for determining how peer support interventions affect adolescents living with HIV. Purpose: Assessing the impact of peer support interventions on HIV-positive adolescents' self-efficacy is essential. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Adolescents with HIV, I: Peer support intervention, C: Individual counseling, standard education, or regular therapy, O: Improving self-efficacy, S: Randomized controlled trials. The article search was conducted systematically using the keywords: “Peer Support,” AND “Self-efficacy,” AND “Adolescents” AND “HIV.” Results: Among adolescents with HIV, the peer support intervention demonstrated an increase in self-efficacy. Participants reported feeling more confident in managing their treatment and navigating daily challenges related to their condition. The supportive peer environment helped reduce feelings of isolation and encouraged adherence to antiretroviral therapy (ART). Conclusion: Peer support interventions effectively enhance self-efficacy in adolescents living with HIV by improving confidence in treatment management, stigma coping, and ART adherence. Their empathetic, equal, and communicative approach makes them more acceptable to adolescents who may be reluctant to share with professionals.